A Study of Poly-Ferric-Aluminum-Silicate-Sulfate: Preparation, Characterization and Application - Chen1, Wei; Zheng1, Huaili; Sun1, Yongjun; Zhou1, Yuhao; Zhang3, Yuxin; Zhao1, Chun; Tang1, Xiaomin; Zhai1, Jun; Xue1, Wenwen (Asian Journal of Chemistry, 2014)
Coagulation-flocculation process is of great significance to water/wastewater treatment facilities. In this study, an effective composite coagulant poly-ferric-aluminum-silicate-sulfate was prepared with water glass, FeSO4·7H2O, Al2(SO4)3·18H2O and NaClO3 as raw materials. Infrared spectra, scanning electron microscopy and Ferron analysis methods was adopted to characterize the poly-ferric-aluminum-silicate-sulfate under different Si/(Fe+Al) and OH/(Fe+Al) molar ratio. Coagulation behaviour of poly-ferric-aluminum-silicate-sulfate used in domestic wastewater treatment was extensively studied in a jar test by measuring turbidity, removal efficiency of chemical oxygen demand as well as zeta potential, sludge volume, flocs size (d50). The analysis of infrared spectra and scanning electron microscopy picture showed that the poly-ferric-aluminum-silicate-sulfate is a complex compound of Si and the metal ions. Ferron analysis results demonstrated that the species distribution of poly-ferric-aluminum-silicate-sulfate corresponded to Si/(Fe+Al) and OH/(Fe+Al) molar ratio at early aging stage, but the relationship was not well related with aging time. Coagulation experiment suggested that when Si/(Fe+Al) was 1:9 and OH/(Fe+Al) was 0.3, the coagulant exhibited superior water treatment performance. The optimal poly-ferric-aluminum-silicate-sulfate produced more sludge volume than polyaluminium silicate, but much less than other Fe-based coagulant. In addition, the coagulation mechanisms in water treatment process were found to be the adsorption/bridge formation and in a lesser extent, the adsorption/charge neutralization mechanism.